Variabilidade espacial e temporal das propriedades químicas do solo e das folhas, qualidade do fruto e produtividade em pomar de laranja Monte Parnaso - Suszek, Grazieli (2012)
The plant nutritional quality influences directly in juice quality. Therefore it is important the knowledge of its spatial and temporary variation in the orchard for a better application and use of the inputs, larger yield and quality of fruit. This way, input maps can be generated for the best use, providing larger yield and better quality of fruits, reduction of the production cost and environmental impact. The objective of this work was to study the spatial variability of soil and plant chemical properties, fruit quality, and orchard yield in Monte Parnaso citrus orchard, by using nutritional sufficiency range and diagnose recommendation integrated system (DRIS). For that, the experiment was driven in an orange-tree orchard (1 ha) of Monte Parnaso variety, located in Nova Laranjeiras/PR. Twenty trees were georeferenced, to collect samples for accomplishment of soil analysis, leaf analysis and quantification of the parameters of fruit quality, in 2009 and 2010. After parameters determination, the results of leaf analysis were evaluated and compared by using sufficiency range and DRIS. For the spatial variability Investigation, it was used the spatial dependence index (IDE) and global correlation of Moran index. The maps were constructed by using geostatistical techniques and compared by using coefficient of relative deviation (CDR). Thus, the sample collection made in branches without fruit (July) presented the best coefficient of determination and the best fit around the trend line for the method DRIS, compared to the samples collected in branches with fruit (January). The ratio (SST/ATT) has better relationship with IBN (nutrient balance index), compared to the productivity and thus presents a better response in the choice of standard population to calculate the DRIS. For the definition of management zones, it is possible to say that the maps were reclassified by DRIS showed best performance since, and greater sensitivity in the diagnosis when compared to bands of sufficiency, which is desirable when seeking to refine the nutritional management.